Proceedings Sixth International Symposium on High-Performance Computer Architecture. HPCA-6 (Cat. No.PR00550)
DOI: 10.1109/hpca.2000.824337
|View full text |Cite
|
Sign up to set email alerts
|

Design of a parallel vector access unit for SDRAM memory systems

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…One key idea is to group together memory accesses with the same access type and similar addresses by reordering, in order to minimize the performance degradation due to various timing constraints on DRAM accesses. There have been proposals to exploit these characteristics to achieve higher performance on vector [21], stream [32], and single-core and multicore processors [26,27]. Higher performance typically leads to higher energy efficiency by reducing execution time and saving static power.…”
Section: Related Workmentioning
confidence: 99%
“…One key idea is to group together memory accesses with the same access type and similar addresses by reordering, in order to minimize the performance degradation due to various timing constraints on DRAM accesses. There have been proposals to exploit these characteristics to achieve higher performance on vector [21], stream [32], and single-core and multicore processors [26,27]. Higher performance typically leads to higher energy efficiency by reducing execution time and saving static power.…”
Section: Related Workmentioning
confidence: 99%
“…In technology, DRAM latency is improved by 7% every year, which is much slower than that of processor. In computer architecture, many architecture-level mechanisms have been employed or studied at the DRAM level to improve performance, such as latency reduction and data transfer rate improving techniques [50,20,21,40,41,39,45,46], and memory access scheduling [44,36,35,37,38,17,49,48,5,59,34,58,7,60,19,47,53].…”
Section: Thermal Issue Of Ddr2 and Fully Buffered Dimm (Fbdimm) Memoriesmentioning
confidence: 99%
“…However, it has been shown that better memory scheduling approaches can substantially improve performance [30,6,28,33,16]. Such approaches improve performance by reducing gaps between commands.…”
Section: Related Workmentioning
confidence: 99%